STUDENTS’ PERSPECTIVE ON REFERENCE AND WRITING STRATEGIES IN AVOIDING PLAGIARISM - Abdurrahman Hidayat; Eko Suhartoyo; Dzul Fikri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: In academic writing, incorporating source from previous research and expert is essential to support an article. However, improper use of other’s works might cause plagiarism. it is important to understand what is plagiarism and strategies to avoid it. This study aims to identify students’ perception about source incorporation, plagiarism and unintentional plagiarism due to error in writing as well as the strategies that they use to avoid plagiarism. This study use narrative qualitative framework and semi structural interview as instrument of data collection. Research data collected from 10 late-semester students of English department from University of Islam Malang. The result shows that most students understands about plagiarism and incorporation of other’s idea, but participants only mention problems related to textual plagiarism, and none mention about plagiarism of idea or self-plagiarism. To avoid plagiarism, each participant use directquotation technique properly, but not everyone paraphrase and summarize effectively. Every participant has shown no intention to transgress in academic writing that indicates strong influence of prevention rules regarding plagiarism. Key Words: Academic Writing, Referencing Strategies, Plagiarism